A Novel Human Long Noncoding RNA SCDAL Promotes Angiogenesis through SNF5‐Mediated GDF6 Expression. Issue 18 (28th July 2021) - Wu, Rongrong; Hu, Wangxing; Chen, Huan; Wang, Yingchao; Li, Qingju; Xiao, Changchen; Fan, Lin; Zhong, Zhiwei; Chen, Xiaoying; Lv, Kaiqi; Zhong, Shuhan; Shi, Yanna; et al.
Abstract: Angiogenesis is essential for vascular development. The roles of regulatory long noncoding RNAs (lncRNAs) in mediating angiogenesis remain under‐explored. Human embryonic stem cell‐derived mesenchymal stem cells (hES‐MSCs) are shown to exert more potent cardioprotective effects against cardiac ischemia than human bone marrow‐derived MSCs (hBM‐MSCs), associated with enhanced neovascularization. The purpose of this study is to search for angiogenic lncRNAs enriched in hES‐MSCs, and investigate their roles and mechanisms. AC103746.1 is one of the most highly expressed intergenic lncRNAs detected in hES‐MSCs versus hBM‐MSCs, and named as SCDAL (s tem c ell‐d erived a ngiogenic l ncRNA). SCDAL knockdown significantly reduce the angiogenic potential and reparative effects of hES‐MSCs in the infarcted hearts, while overexpression of SCDAL in either hES‐MSCs or hBM‐MSCs exhibits augmented angiogenesis and cardiac function recovery. Mechanistically, SCDAL induces growth differentiation factor 6 (GDF6) expression via direct interaction with SNF5 at GDF6 promoter. Secreted GDF6 promotes endothelial angiogenesis via non‐canonical vascular endothelial growth factor receptor 2 activation. Furthermore, SCDAL‐ GDF6 is expressed in human endothelial cells, and directly enhances endothelial angiogenesis in vitro and in vivo. Thus, these findings uncover a previously unknown lncRNA‐dependent regulatory circuit for angiogenesis. Targeted intervention of the SCDAL ‐GDF6 pathway has potential as a therapy for ischemic heart diseases. Abstract : Long noncoding RNA (lncRNA) SCDAL (s tem c ell‐d erived a ngiogenic l ncRNA) is identified as a critical regulator for angiogenic actions of human embryonic stem cell‐derived mesenchymal stem cells (hES‐MSCs) in ischemic hearts. SCDAL initiates growth differentiation factor 6 (GDF6) expression by recruiting SNF5 to GDF6 promoter. Secreted GDF6 promotes endothelial angiogenesis through vascular endothelial growth factor receptor 2 pathway.